Một số tính chất của quá trình thừa kế kiểu trong mô hình cơ sở dữ liệu hướng đối tượng - Ban, Đoàn Văn (Journal of Computer Science and Cybernetics, 2016)
Inheritance is introduced in object-oriented systems to enhance code reuse and create more compact and open able software [2], [3], [7]. Powerful object models adopt multiple inheritance, allowing a type (or class) to inherit from more than one supertype. Unfortunately, this powerful modeling mechanism can generate inheritance conflicts [6], which arise when the same property (or operation) is defined in more than one supertype, or a property (or operation) already present in one supertype, is locally redefined in subtype (overriding). In this article, we focus on the structural component of object-oriented database schema, addressing inheritance and conflict resolution for typed properties.